1996
DOI: 10.1161/01.hyp.28.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Invasive Hemodynamic Measurements at Rest and During Exercise in Hypertensive Men

Abstract: In 1994, we ascertained the outcome of 143 hypertensive men in whom invasive hemodynamic measurements were performed at rest and during graded bicycle exercise during the period 1972-1982 to assess (1) which of the hemodynamic components of blood pressure is associated with the incidence of cardiovascular events and total mortality, and (2) whether the hemodynamic response to dynamic exercise adds prognostic precision to the data at rest. During 2186 patient years of follow-up, 38 patients suffered at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
11

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 19 publications
2
56
1
11
Order By: Relevance
“…Studies that reported positive associations between LV mass and exercise BP included only men, 7,8 while other studies that did not show such an association included both genders. 9,10 In our study, the correlation between exercise SBP and LV mass was stronger in men than in women. While the relation of exercise SBP and LV mass was not significantly different between genders in multivariate model, the bivariate correlations were statistically significant in men but not in women.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Studies that reported positive associations between LV mass and exercise BP included only men, 7,8 while other studies that did not show such an association included both genders. 9,10 In our study, the correlation between exercise SBP and LV mass was stronger in men than in women. While the relation of exercise SBP and LV mass was not significantly different between genders in multivariate model, the bivariate correlations were statistically significant in men but not in women.…”
Section: Discussionmentioning
confidence: 42%
“…4 An exaggerated BP response to exercise is a known marker for future hypertension [5][6][7][8] and increased mortality. [9][10][11] Since BP during exercise reflects cardiac load during a period of high demand for cardiac output, it may be a more sensitive predictor of LV mass than resting BP. Several studies have addressed the importance of BP responses to exercise in relation to LV mass.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in vascular resistance may result in greater benefits in reducing cardiovascular risk than improvement in BP alone, 24 and differences in SVRI at the same BP may explain poorer prognosis for men versus women 25 and black versus nonblack patients. 26 Hemodynamics are also known to change with age.…”
Section: Smith Et Al Noninvasive Hemodynamics and Bp Control 775mentioning
confidence: 99%
“…Wyniki badań dotyczących prognostycznego znaczenia BP podczas wysiłku fizycznego również nie są zgodne [125], co może wynikać z tego, że podczas dynamicznego wysiłku fizycznego 2 składowe hemodynamiczne BP ulegają zmianom w przeciwnych kierunkach: systemowy opór naczyniowy zmniejsza się, natomiast pojemność minutowa wzrasta. Prawdopodobnie decydującym czynnikiem prognostycznym jest osłabienie zmniejszenia systemowego oporu naczyniowego podczas wysiłku, które wynika z patofizjologicznych zmian strukturalnych w tętnicach i tętniczkach [123,129]. To, czy wspomniane upośledzenie rozkurczu tętnic będzie prowadzić do nadmiernego wzrostu BP, czy też nie, może przynajmniej częściowo zależeć od pojemności minutowej.…”
Section: Ciśnienie Tętnicze Podczas Wysiłku Fizycznego I Innych Testóunclassified
“…W przypadku prawidłowego BP w spoczynku nadciś- nienie wywołane wysiłkiem można uważać za wskazanie do ABPM ze względu na jego związek z nadciśnieniem zamaskowanym [131]. Jeśli natomiast nadciśnienie wiąże się z dysfunkcją serca i zmniejszeniem wzrostu pojemności minutowej w odpowiedzi na wysiłek, to BP podczas wysiłku może tracić znaczenie prognostyczne [129]. Należy wreszcie zauważyć, że wyższe BP podczas wysiłku może się nawet wiązać z lepszym rokowaniem, np.…”
Section: Ciśnienie Tętnicze Podczas Wysiłku Fizycznego I Innych Testóunclassified